15=-3(2q+1)

Simple and best practice solution for 15=-3(2q+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15=-3(2q+1) equation:



15=-3(2q+1)
We move all terms to the left:
15-(-3(2q+1))=0
We calculate terms in parentheses: -(-3(2q+1)), so:
-3(2q+1)
We multiply parentheses
-6q-3
Back to the equation:
-(-6q-3)
We get rid of parentheses
6q+3+15=0
We add all the numbers together, and all the variables
6q+18=0
We move all terms containing q to the left, all other terms to the right
6q=-18
q=-18/6
q=-3

See similar equations:

| –10+2y=y | | 5.8x+5.7=16.4x+3 | | 7x=5(x-5) | | 14-(p+5)=3(p+9)-12 | | 2r=-6+5r | | 15=-3(2q+) | | x=0.3x6x-10=12 | | -2x+-6=-4 | | 5+7z=9z+15 | | 6x-5-9x+2=-9 | | -4.1a=-4.6a-3.15 | | 6(2x-1)-12(x+1)=2x+6 | | 5x−2(x+5)=11 | | b(6)=24 | | -1=8+r-1 | | |2x-4|=|x-9| | | 6p-3=2p+5 | | 8a−(1+5a)=12a−64 | | 3b+9=9b-81 | | 11x+18=11x-7 | | 9x+1/9=x/2+2 | | 5+(-7)=r | | 1x+9.5=1.5x+6.5 | | 4x+(x+7)=42 | | -15+18a=13-10a | | 0=-p+p | | 6n-3n=3(n-2)-2(-3+3n) | | 160+12m=400 | | 20x–3+5x=22 | | -9k=-9k-2 | | 10x+-8x=2x-1 | | –3g=–2−g |

Equations solver categories